Sensors Proceedings of the Fourth National Conference on Sensors, February 21-23, 2018, Catania, Italy - Andò, Bruno; Baldini, Francesco; Di Natale, Corrado; Ferrari, Vittorio; Marletta, Vincenzo; Marrazza, Giovanna; Militello, Valeria; Miolo, Giorgia; Rossi, Marco; Scalise, Lorenzo; Siciliano, Pietro (Lecture Notes in Electrical Engineering, 2019)
This book gathers the best papers presented at the Fourth Italian National Conference on Sensors, held in Catania, Italy, from 21 to 23 February 2018. The book represents an invaluable and up-to-the-minute tool, providing an essential overview of recent findings, strategies and new directions in the area of sensor research. Further, it addresses various aspects based on the development of new chemical, physical or biological sensors, assembling and characterization, signal treatment and data handling. Lastly, the book applies electrochemical, optical and other detection strategies to relevant issues in the food and clinical environmental areas, as well as industry-oriented applications.